Endo-siRNAs regulate early embryonic development by inhibiting transcription of long terminal repeat sequence in pig†. Issue 6 (18th March 2019) - Kong, Qingran; Quan, Xue; Du, Jiawei; Tai, Yurong; Liu, Wanxin; Zhang, Jiaming; Zhang, Xiaolei; Mu, Yanshuang; Liu, Zhonghua
Abstract: Activity of some endogenous retroviruses (ERVs) has been proven to be important for development of early mammalian embryo. However, abnormal activation of ERVs can also cause genetic diseases due to their ability to retrotranspose, so the regulatory mechanism to limit transcription of ERVs needs to be clarified. Endogenous small interfering RNA (endo-siRNA) has been reported to protect cells against transposable elements (TEs). Here, we determined the role of ERVs long terminal repeat sequences (LTRs) derived endo-siRNAs (LTR-siRNAs) on inhibition of the activity of ERVs during early embryonic development in pig. Seven most highly expressed LTR-siRNAs were identified in porcine zygote by high-throughput small RNA sequencing. We verified that the biogenesis of the LTR-siRNAs was DICER-dependent and they were generated from double-stranded RNA (dsRNA) formed by sense and antisense transcripts of LTRs. And, the expression of sense and antisense of LTRs might be due to the loss of DNA methylation at some LTR loci. Furthermore, we showed that the LTR-siRNAs could regulate early embryonic development by repression of LTRs expression at a post-transcriptional level. So, we propose here, during early embryonic development when epigenetic reprogramming occurs, the endo-siRNA pathway acts as a sophisticated balance of regulatory mechanism for ERV activity. Abstract : Endo-siRNAs function on early embryos in pig.